Knowledge, attitude and practice of vaccinators and vaccine handlers on vaccine cold chain management in public health facilities, Ethiopia: Cross-sectional study. - Solomon Ahmed Mohammed; Birhanu Demeke Workneh; Mesfin Haile Kahissay (PLoS ONE, 2021)
Background Effective management of the vaccine cold chain system at all levels is one of the crucial factors for maintaining vaccine potency. Vaccines require more complex handling and storage requirements due to increased temperature sensitivity and complicated immunization schedules. This urges adequate knowledge, attitude, and practice. This study assessed the knowledge, attitude, and practice of vaccinators and vaccine handlers' in public health facilities. Methodology An institutional-based cross-sectional study design was used to assess the knowledge, attitude, and practice of 127 vaccinators and vaccine handlers in public health facilities of Oromia Special Zone, from September 1 to 30, 2019. Data were collected using self-administered questionnaires and a structured observation checklist. Descriptive and inferential statistics were made using the statistical package for social sciences version 20. Variables with a p-value <0.05 were taken as statistically significant. Result The response rate was (96.94%). Sixty-eight (53.5%; 95% CI: 46.5%, 61.4%), 58 (45.7%; 95% CI: 37.8%, 53.5%) and 62 (48.8%: 95% CI; 41.7%, 56.7%) vaccinators and vaccine handlers had satisfactory knowledge, positive attitude and good practice respectively. Receiving training on cold chain management had a statistically significant association with the level of knowledge on cold chain management (AOR = 3.04, 95% CI: 1.04-8.88). Conclusions More than half of vaccinators and vaccine handlers had satisfactory knowledge, while below half of vaccinators and vaccine handlers had a positive attitude and good practice. The determinants of knowledge in cold chain management were receiving training on cold chain management. Providing regular technical support and on the job training on vaccine cold chain management will improve the knowledge, attitude, and practice of vaccinators and vaccine handlers.